Urgensi Ekonomi Islam dalam Pengembangan Perbankan Syari’ah di Indonesia - Mujahidin, Akhmad (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
Economic goals of Islam is that every human activity is based on devotion to God and in order to carry out the task of God for the prosperity of the earth, then in berekonomi Muslims should prioritize harmony and nature conservation. Pursued happiness in Islam is not merely the happiness in the world, but also happiness in the Hereafter. Thus Islamic economics must have an economic system that can prosper the earth, human beings capable of happiness both for living in the world and in the hereafter. Islamic economic outlook has a very high prospect and promising, if the network constraints can be overcome, it can be believed to be a great opportunity. It can be seen from the enthusiastic response of the community in economic activity using Islamic principles as well as the positive trend in the non-financial / economic, such as the education system, laws and others that support the development of national Islamic economics.